NEW ARCHOSAURS FROM THE JURASSIC OF SIBERIA AND MONGOLIA - Kurzanov S.M.; Efimov M.B.; Gubin Y.M. (My University, 2003)
New finds of crocodiles and dinosaurs from the Late Jurassic deposits of southwestern Mongolia (Shar-Teg locality) and Eastern Siberia (basin of the Vilyui River, Teete locality) are described. A new species of small-sized running crocodiles, Nominosuchus arcanus, characterized by a small number of teeth is described from the Shar-Teg locality on the basis of the anterior parts of the skull. A Jurassic assemblage of dinosaurs, including Stegosaurus sp., sauropods resembling Camarasaurus, and predatory theropods, including Allosaurus sp., is established for the first time on the basis of the material from the Teete locality in Siberia. This corroborates the presence of the Zoogeographic relationship between the North American and Siberian faunas at that time.
Keywords: Jurassic; Mesozoic::Jurassic; Мезозой::Юрская